Competencia laboral y calidad de servicio en los empleados de Samiria Jungle Hotel, Iquitos 2023 - Alvarez Diaz, Genesis de Jesus (2024)
The study objective of the report was to determine the relationship between labor competence and quality of service in employees of Samiria Jungle hotel, Iquitos 2023. We opted for an applied type study accompanied by a non[1]experimental design, taking as a sample 150 guests, to whom a questionnaire was applied for the collection of information. Obtaining as results that, labor competence was qualified as regular by 37% of the guests and 36% considered it adequate. On the other hand, the quality of service is perceived as good by 33% of respondents and followed by 32% rating it as fair. Finally, I conclude that there is a direct and significant correlation between labor competence and quality of service at the Samiria Jungle Hotel, Iquitos, during 2023, supported by a Rho coefficient of 0.643 and a significance level of 0.000. Likewise, the identification, standardization and formation of competencies have a positive influence on the quality of service, with Rho coefficients of 0.549, 0.579 and 0.648, respectively.